1997
DOI: 10.1159/000164110
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Cytokeratins 14, 18 and 19 Correlates with Tumor Progression in the Uterine Cervix

Abstract: The expression of cytokeratins (CKs) in normal cervical ephitelium, low grade squamous intraepithelial lesions (SIL), high grade SILs and squamous cell carcinoma (SCC) were analyzed using four different monoclonal antikeratin antibodies. In normal cervical epithelium, CK 18 showed strong immunoreactivity in basal and parabasal layers. CK 19 and 14 were expressed only in the basal layer while CK 13 was found selectively in the spinal cells. As the lesions progressed from low grade SIL to high grade SIL, immunor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Up to now analyses of the specific epithelial keratin profile in HPV infected oral mucosa and in HPV related oral and oropharyngeal cancers are scanty and questionable. Although it is well known that CK19 and/or its fragment CYFRA 21–1 correlate with tumor progression both in the uterine cervix and in the upper aerodigestive tract [ 31 – 33 ] and are statistically significantly connected to patients outcome [ 34 36 ], the exact role of CK19 in the genesis of HPV related oral and oropharyngeal cancer requires further assessment [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now analyses of the specific epithelial keratin profile in HPV infected oral mucosa and in HPV related oral and oropharyngeal cancers are scanty and questionable. Although it is well known that CK19 and/or its fragment CYFRA 21–1 correlate with tumor progression both in the uterine cervix and in the upper aerodigestive tract [ 31 – 33 ] and are statistically significantly connected to patients outcome [ 34 36 ], the exact role of CK19 in the genesis of HPV related oral and oropharyngeal cancer requires further assessment [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…If we assume proper sample collection in every case, it is confounding why samples with advanced lesions (C1, C4, C6-C9) or even cancer (C2, C3) would show such low levels of keratins 5, 8, and 18. One would be inclined to expect the opposite, as dyplastic cells harboring these basal keratins should increase with disease progression [24,29,30,32]. Nevertheless, we do see cases where proper samples have not necessarily been obtained.…”
Section: Discussionmentioning
confidence: 73%
“…Although their biology is complex and over 50 functional keratin genes exist, studies have shown general expression patterns in normal cervical epithelium [27]. "Maturation" keratins normally present in differentiated intermediate and superficial squamous cells include keratins 4, 10, and 13, while stably expressed keratins localized to undifferentiated basal/parabasal/ reserve, squamous metaplastic, and endocervical columnar cells include keratins 5, 8, and 18 [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In molecular terms, it seems that CK19 might free the viral E7 mRNA from the translational block exerted by the CK7,7 thus leading to increased E7 protein level and, eventually, to the possibly related carcinogenic events. Indeed, CK19 and/or its fragment CYFRA 21‐1 correlate with tumor progression in the uterine cervix and the upper aerodigestive tract13, 14, 15 and are significantly connected to both disease‐free interval and survival of patients 16, 17, 18. In addition, wild‐type p53 inhibits CK19 expression with concomitant reconstruction of an epidermis more similar to that obtained with normal keratinocytes and characterized by the inversion of the proliferative compartment and the abnormal expression of CK19 19.…”
mentioning
confidence: 99%